Photocatalytic Degradation Of Methylene Blue By Using WO3/g-C3N4 Catalyst Under Visible Light - Md Isa, Abdul Aziz (Universiti Sains Malaysia, 2018)
WO3/g-C3N4 catalyst coupled with various WO3 loadings (0.5 – 1.5 mol%) were successfully prepared by impregnation method. The prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive X-ray (EDX), surface characteristics and UV-vis reflectance spectra. In this study, XRD result showed that the addition of WO3 loading in catalyst preparation did not give any significant peak of WO3 due to the less amount of WO3 than g-C3N4. Photocatalytic test revealed that 1.5 mol% WO3/g-C3N4 catalyst gave the highest degradation efficiency. The performance of prepared photocatalyst was evaluated by monitoring the degradation of methylene blue under visible light. Three process variables were studied; effect of catalyst loading, effect of initial methylene blue concentration and effect of dissolved oxygen. The optimum conditions obtained as followed: catalyst loading of 2.0 g/L, initial concentration of methylene blue 10 mg/L and dissolved oxygen of 10 cm3/min. Kinetic for degradation of methylene blue also has been studied. Result showed that the reaction kinetic for this study followed pseudo-first order kinetic with kapp was 0.0057 min-1. The catalyst shows repeatability characteristics as it possess higher than 84 % degradation efficiency after 3 cycles.